“About Navigating Chaos”: Latin American and Caribbean Mental Health Workers’ Personal Impact Due to SARS-CoV-2 in the First Hundred Days - Agrest, Martin; Rosales, Melina; Fernández, Marina; Kankan, Tanvi; Matkovich, Andrés; Velzi-Díaz, Alberto; Ardila-Gómez, Sara (International Journal of Public Health, 2022)
Objectives: The personal impact of COVID-19 on mental health care workers (MHWs) has received scarce attention despite their work addressing the emotional wellbeing of those affected by the pandemic. This study aims to analyze Latin American and Caribbean’s MHWs’ subjective impact in connection to working during the initial times of the pandemic. Methods: One hundred and fifty-five persons (n= 155) from seventeen countries were contacted in May - June 2020 through a snowball approach. Complementary methodological strategies of analysis used for data triangulation included content analysis, thematic analysis, and interpretative phenomenological analysis. Results: Participants reported feelings of fear, anxiety, anguish, and fatigue. Milder negative impacts (e.g., uncertainty, concern), and complex feelings (e.g., ambivalence) were also frequent. One third of participants acknowledged their capacity to learn from this situation and/or experience satisfaction. Conclusion: Mental health of MHWs in Latin America and the Caribbean were under severe strain and the ongoing mental health reforms at risk during the pandemic’s beginning. More research and additional care may be needed to offer support to those involved in caring for the wellbeing of others.